108 The relation between change in left ventricular systolic function and subsequent mortality in patients with chronic heart failure. (6th June 2022) - Brown, Oliver; Sklirou, Maria; Cuthbert, Joe; Abel, Alexandra; Samuel, Nathan; Kazmi, Syed; Clark, Andrew
Abstract : Introduction: Increasing severity of impairment of left ventricular systolic dysfunction (LVSD) in patients with chronic heart failure (CHF) is associated with higher mortality. However, the relation between temporal changes in LVSD severity and long-term clinical outcome is unknown. MethodsPatients with CHF defined as the presence of compatible symptoms and either at least moderate LVSD or NTproBNP >125 ng/L were enrolled. LVSD was qualitatively assessed as: none, mild, moderate, and severe. Echocardiography was performed at baseline and 12 months. The primary endpoint was all-cause mortality. Cox proportional hazard models were used to assess the relation between changes in LVSD and outcome. Hazard ratios (HR) are reported with 95% confidence intervals (CI).Results At baseline, 170 (11%) had no, 231 (16%) mild, 633 (43%) moderate and 453 (30%) severe LVSD. Amongst patients with either moderate or severe LVSD at baseline, 40% had improvement in function at 12 months (figure 1). Amongst patients with no LVSD at baseline, only 14% had deterioration of function. During subsequent median follow up of 2773 days, 868 patients died. Worsening of LVSD was associated with increasing all-cause mortality in patients with moderate LVSD and severe LVSD at baseline (figure 2), but this was not significant after adjustment for covariables (table 1). Improvement of LVSD was independently associated with better survival in patients with moderate LVSD at baseline (HR 0.72 (95% CI: 0.53–0.98, p = 0.04). Conclusion: Greater severity of LVSD at baseline is associated with increasing likelihood of improvement. Amongst patients with moderate LVSD, improvement in LVSD is independently associated with survival. Conflict of Interest: Funded by the National Institute for Health Research